Medication Adherence and the Role of Pictograms in Medication Counselling of Chronic Patients: a Review - Merks, Piotr; Cameron, Jameason; Bilmin, Krzysztof; Świeczkowski, Damian; Chmielewska-Ignatowicz, Tomira; Harężlak, Tomasz; Białoszewska, Katarzyna; Sola, Katarina Fehir; Jaguszewski, Miłosz J; Vaillancourt, Regis (Frontiers in Pharmacology, 2021)
Pharmaceutical care requires a patient-centered approach, focusing on the ability of patients to understand drug-related information and follow the instructions delivered by pharmacists as well as other health-care providers included in the circle of care. With the goal of ensuring the prescribed use of medications, called medication adherence, health-care providers have to consider many risk factors such as geography (culture), social economic status, age, and low literacy that may predispose patients to non-adherence, and considerations have to be made for chronic patients living with life-long disease states. The aim of this review is to provide a balanced and comprehensive review outlining a number of different medication counselling and education approaches that have been used to try to improve medication adherence and health outcomes with the use of clear and concise graphic illustrations—called pictograms. By highlighting the current landscape of the general use and efficacy of pharmaceutical pictograms to aid in the knowledge and recall of drug-related information, as well as outlining specific medication adherence outcomes with pharmaceutical pictograms in chronic patients, the current review describes the need for health-care providers to move beyond the traditional didactic methods of oral and verbal communication with patients regarding medication-taking behavior.